Examining Ambiguity and Social Ties among Institutionalized Older Adults: A Sociological Interrogation - Satish Kr Gupta (Journal of the Indian Academy of Geriatrics)
Introduction: The increasing prevalence of old age homes in urban India reflects changing family dynamics and growing needs for elder care. Older adults residing in such institutions often grapple with complex emotional, social, and existential challenges. This study investigates the multifaceted nature of ambiguity in their lives and explores the role of social ties in shaping their experiences within institutional settings. Aims and Objectives: • To explore the nature and extent of ambiguity experienced by institutionalized older adults. • To investigate the role of social ties and networks in the lives of institutionalized older adults. • To analyse the impact of disrupted social networks on the self-perception and identity of older adults. • To assess the coping mechanisms employed by older adults to manage ambiguity and social disconnection. Materials and Methods: This qualitative study was conducted in a selected old age home in Lucknow, Uttar Pradesh. Data was collected through an extensive literature review, in-depth interviews, and detailed case studies with older adult residents. Thematic analysis was employed to identify recurring patterns, sources of ambiguity, and the nature of social connections within institutional life. Results: The study reveals that ambiguity in the lives of institutionalized older adults stems largely from uncertainty about the future, perceived abandonment by family, and existential concerns related to purpose and identity. However, meaningful social ties—whether with peers, caregivers, or through sporadic family interactions—serve as critical buffers, helping residents navigate emotional complexities. Institutions that adopt inclusive and participatory practices foster stronger social bonds, greater psychological resilience, and a sense of belonging among residents. Conclusion: The findings underscore the vital role of social integration and supportive relationships in mitigating the negative impacts of ambiguity among older adults in institutional settings. This research offers evidence-based insights for policymakers, social workers, and institutional administrators to develop more responsive elder care models. Emphasizing inclusivity, empathy, and emotional support can significantly enhance the quality of life and mental well-being of institutionalized older adults, contributing to broader goals of social sustainability and reduced inequalities.